Interference effects in electron capture from insulator surfaces - Gravielle, Maria Silvia (2005)
We investigate the electron capture from insulator surfaces under grazing impact conditions. The eikonal-impulse approximation is used to describe coherent electron exchange from surface ions. In the model the transition amplitude is expressed as the sum of atomic transition amplitudes, each one associated with capture from a different lattice site. The method is applied to 100 keV protons colliding on LiF surfaces. Strong interference effects as a function of the crystal orientation were found for the partial capture from a given initial crystal state. However, these interference structures disappear when the contributions from different crystal states add up to obtain the total capture probability from the surface band.